Correlation study of PBK/TOPK expression, prognosis, and immune infiltration in breast cancer - Bingxin Li; Tianze Yao; Min Zhang; Jiaxuan Yu; Jiping Xie; Yi Wan; Yuchuan Ge; Guangze Sun; Yongqiang Yao (Scientific Reports)
Abstract PDZ-binding kinase/T-lymphokine-activated killer-cell-originated protein kinase (PBK/TOPK) is a serine-threonine protein kinase. This study aimed to investigate the expression pattern, prognostic significance, and relationship with tumor immune infiltration of PBK/TOPK in breast cancer through bioinformatics analyses and immunohistochemistry (IHC), providing insights for individualized treatment and immunotherapy strategies. PBK/TOPK expression and its correlation with clinicopathological features were analyzed using TIMER, UALCAN, and TCGA databases. Prognostic value was assessed via Kaplan–Meier plotter and bc-GenExMiner. Variants of the PBK/TOPK gene and their prognostic implications were explored using cBioPortal. Enrichment analysis in R identified signaling pathways linked to PBK/TOPK. The relationships between PBK/TOPK, tumor-infiltrating lymphocytes (TILs), and immune cell markers were evaluated using TIMER and TISIDB. IHC experiments validated PBK/TOPK expression in tumor samples and its association with prognosis. Meanwhile, IHC also further confirmed the correlation between PBK/TOPK and CD4+ and CD8+ T cells infiltration, as well as the relationship between T cells and breast cancer prognosis. PBK/TOPK was significantly overexpressed in breast cancer tissues compared to normal tissues and correlated with clinicopathological features, including tumor size and lymph node stage. High expression of PBK/TOPK was associated with poor prognosis. While breast cancer subtypes exhibited different PBK/TOPK gene variants, these variants did not influence prognosis. PBK/TOPK is involved in cell meiosis, cytoskeletal motility, and pathways such as FoxO and p53. It is associated with immune infiltration and is differentially expressed in breast cancer subtypes and correlates with TILs and immune cell markers. IHC confirms that PBK/TOPK expression positively correlates with CD4+ T and CD8+ T cells infiltration. CD4+ T cells were positively associated with the prognosis of triple-negative breast cancer. PBK/TOPK is overexpressed in breast cancer tissues, and high expression levels are associated with poor patient prognosis. Additionally, PBK/TOPK is linked to immune infiltration in breast cancer, positively correlating with CD4+ and CD8+ T cells infiltration, suggesting a new avenue for immunotherapy research in breast cancer.